Effect of enhanced recovery after surgery (ERAS) pathway on the postoperative outcomes of elbow arthrolysis: A randomized controlled trial. (August 2019) - Cui, Haomin; Sun, Ziyang; Ruan, Jihao; Yu, Yaling; Fan, Cunyi
Abstract: Background: Enhanced recovery after surgery (ERAS) protocols aim to improve perioperative outcomes and facilitate recovery for the patient through multimodal pathways. While implementation of ERAS has improved outcomes in numerous surgical specialties, benefits specific to elbow arthrolysis have not been investigated. The purpose of this study was to determine the effects of an evidence-based ERAS pathway on: (1) reducing pain intensity and postoperative complications compared to conventional care, and (2) improving range of motion (ROM) and function of the elbow after open arthrolysis. Methods: A randomized controlled study was performed between September 2017 and January 2018. Fifty patients with post-traumatic stiff elbow scheduled for surgery were randomly divided into ERAS group (25 patients) and conventional care group (25 patients). Duration of surgery, pre- and post-surgery ROM, Mayo Elbow Performance Score (MEPS), and visual analog scale (VAS) pain scores at rest and in motion were measured postoperatively at 1 through 5 days, 6-weeks, and 6-months. Complications were recorded 6-months postoperatively. Results: VAS pain score values at rest and in motion in the ERAS group were consistently significantly lower than those in the conventional care group at 1 through 5 postoperatively days (P < 0.05). At 6-weeks and 6-months after surgery, pain score values at rest and in motion were similar between the 2 groups (P > 0.05). ROM was consistently significantly better in the ERAS group compared with the conventional care group (P < 0.05). No significant differences in MEPS or complications were found between the 2 groups (P > 0.05). Conclusion: ERAS pathway is feasible to implement in elbow arthrolysis and can result in clinically meaningful improvements in levels of pain (at rest and in motion) and ROM without an increase in the rate of postoperative complications. Highlights: Enhanced recovery after surgery protocols is feasible to implement in elbow arthrolysis. Enhanced recovery after surgery pathway can relieve pain intensity and improve elbow function. Supervising compliance is an important element in Enhanced recovery after surgery protocols implementation.